ANALISIS KEMAMPUAN PEMECAHAN MASALAH SPLDV MENGGUNAKAN INDIKATOR SOEMARMO - Septiarie Rahmawati; Hartatiana -; Muslimahayati - (Universitas Sriwijaya, 2021)
This study aimed to analyze the mathematics problem solving ability of the SPLDV material in class VIII students of SMP Muhammadiyah 8 Palembang according to Hendriana and Soemarmo indicators. The type of research used was qualitative with a descriptive approach. The instruments in this study used written test questions and interviews. The subjects in this study were students of class VIII B of SMP Muhammadiyah 8 Palembang, then the sample of 5 people for interview was selected using purposive sampling technique based on the results of written test scores. The results showed that the level of mathematics problem solving ability of class VIII B students was low. The students who were able to answer questions on indicator 1 were 58.17%, then indicators 2 and 3 were 23.53%, and questions with indicator 4 were 10.39%.